(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Tambovskaya K. V. Intellectual culture and intellectual development of specialist as a strategic aim of quality pedagogical education. Studying of a problem of definition of intellectual culture, which is considered by us as difficult personal education and is defined proceeding from etymology of the concepts «intelligence» and «culture», considers specifics of professionally meaning lines of the identity of future elementary school teacher, provides realization of certain functions in system of professional activity and the sphere of private life.